Evaluating the role of Tregs in the progression of multiple myeloma. Issue 9 (29th July 2019) - Lad, Deepesh; Huang, Qing; Hoeppli, Romy; Garcia, Rosa; Xu, Lixin; Levings, Megan; Song, Kevin; Broady, Raewyn
Abstract: The role of regulatory T-cells (Treg) and Th17 cells in the progression of multiple myeloma has been unclear. There are conflicting reports of the Treg and Th17 frequency being increased, decreased, and unchanged as compared with controls. In this study, we sought to characterize the T-cell subsets including Treg function in both blood and marrow compartments of monoclonal gammopathy of undetermined significance (MGUS) and multiple myeloma (MM). The Treg/Th17 ratio is skewed toward the suppressive phenotype in MGUS and MM. There are more activated and memory Tregs in the myeloma marrow. Although the myeloma Tregs are functional, they are less suppressive than Tregs in chronic lymphocytic leukemia where they drive disease progression. None of the T-cell subsets were found to have a clinical correlation with time to progression in MGUS or progression-free survival in myeloma. Tregs are important but unlikely major players in the progression of MGUS to MM.